Une conséquence de la nouvelle gestion publique : l’émergence d’une pensée comptable en éducation - St-Germain, Michel (Éducation et francophonie, 2001)
It is difficult to understand the major changes in education unless one is looking from a certain distance and adopting a larger vision in relation to the dominant management paradigm. This text presents some theoretical foundations on the New Public Management (NPM), a management paradigm at the base of most of the new reforms in education. The principles can be summarized in a few words: increased decisional participation of the users, who are seen as consumers and electors, the obligation to have quantifiable results, decentralization, increased imputablilty and putting monitoring methods in place. In applying the NPM to education, some facts must be taken into consideration, such as the obligation to measure the performance of the educational system in the context of globalization, the recognition of the individuality of the person, the growing role of parents, the limits of change absorption and finally, the emergence of professionialization.
Publisher: Association canadienne d’éducation de langue française